Mikołaj Grosman (ok. 1380-1442), pleban w Waliszewie, ductor laborum ecclesiae sanctae Trinitatis w Gnieźnie. Przyczynek do średniowiecznej biografistyki - Czyżak, Marta (Ecclesia. Studia z Dziejów Wielkopolski, 2009)
The article – on the basis of documents from The Diplomatic Code of Great Poland and the widely used books of the official’s court in Gniezno – presents the church career and activity of Mikołaj Grosman, the representative of the lower cathedral clergy and the parish clergy as well. Since 1403 he had a benefice (an altar) in the Gniezno cathedral, in 1404 he was mentioned as the chaplain of the Gniezno official Mikoła Strzeszkowic. Even before 1409, he became the parish priest of St. Catherine’s church in Waliszewo, belonging to the Gniezno chapter. He held this function until his death in 1442. In the years 1417–1440 he has repeatedly served as the substitute (locumtenens) of the Gniezno officials. For several years he directed the construction of the parish church of St. Trinity in Gniezno (the right of patronage of the church belonged to the chapter), in 1434 he founded the altar of St. Barbara there. He also founded the carved Group of the Crucifixion for the church in Waliszewo. The article also attempts to sum up the annual incomes of Mikołaj Grosman: examines his revenues from the parish benefice (tithes, missalia) and incomes from the activity in the consistory court. It points out his thrift, which allowed him to expensive foundations.